Evacuation models are running out of time. (November 2015) - Thompson, Peter; Nilsson, Daniel; Boyce, Karen; McGrath, Denise
Abstract: The representation of crowd movement in existing evacuation models is typically based on data collected in the 1950s to 1980s, i.e., data that are more than 40 years old. Since the 1970s, population characteristics have changed dramatically around the world. Reports show that the percentage of elderly and obesity rates have increased significantly and this trend is predicted to continue into the future. Recent research[1–3] illustrates the magnitude by which different age cohorts of a population group can reduce the general speed and flow rates. In addition, well established studies have quantified the impact of body dimensions on speed and flow[4] . However, many existing evacuation models fail to take the changing characteristics of populations into account. This paper aims to review existing knowledge of population demographics and crowd dynamics, derive an indicative flow reduction factor for future populations, and consider the implications for computer models and building design in the future. Graphical abstract: Highlights: Most evacuation models and codes use uniform, standard flows and data from the 1950s to 1980s. The proportion of obese people in the US is due to double from 15% to 30% over 40 years. The proportion of elderly is also due to more than double over the same time. It is postulated that flow may be reduced by as much as 30 or 40%. The standard models and codes take no account of this.